Physical activity in premenopausal women with asymptomatic peripheral arterial disease. Issue 11 (November 2018) - Mattioli, Anna Vittoria; Coppi, Francesca; Migaldi, Mario; Farinetti, Alberto
Abstract : Supplemental Digital Content is available in the text